Comparison of Early Mortality and Morbidity of Off Pump vs On Pump Coronary Artery Bypass Graft Surgery in High-Risk Patients - Nawaz, Atif; Ali , Nasir; Hayat, Sikandar; Sobia, Farah; Sajjad, Ahsan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the early mortality and morbidity of high-risk patients following off-pump and on-pump Coronary Artery Bypass Grafting (CABG). Study Design: Analytical Cross-sectional study. Place and Duration of Study: Tertiary Care Cardiac Center, Rawalpindi Pakistan, from Oct 2022 to Mar 2023. Methodology: Two hundred and forty-three patients undergoing on-pump CABG(ONCAB) or off-pump CABG(OPCAB) with an Ejection Fraction (EF) of <35%, history of stroke, Glomerular Filtration Rate (GFR) <60 ml/min/1.73m2 or a serum creatinine level >1.5 mg/dl, and Chronic Obstructive Pulmonary Disease (COPD) were included using consecutive sampling. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 23:00. Descriptive statistics were used to calculate Mean±SD for continuous variables like (age, EF and duration of hospital stay). Frequencies and percentages were calculated for categorical variables like (gender and post-op outcomes). Chi-square & t-test were used to make comparison between both groups, p-value <0.05 was considered significant. Top of Form. Results: Out of two hundred and forty-three (n=243) patients, 193(79.4%) males and 50(20.6%) females with mean age 49.04±7.75 years underwent ONCAB 150(61.9%) and OPCAB 93(38.1%). ONCAB had slightly higher rates of Myocardial Infarction (5.3%) and Stroke (6%) compared to OPCAB (1.1% for both), p-values of 0.08 and 0.06, respectively. Respiratory complications were more common in ONCAB, with 9.3% requiring re-intubation, compared to 2.2% in the OPCAB group (p=0.02). ONCAB also had a slightly longer hospital stay (7.1±1.4 days) compared to OPCAB (6.7±1.6 days) (p=0.03). Additionally, ONCAB had higher rates of re-..... Conclusion: OPCAB showed lower rates of complications, indicates the...